Application of the TBL teaching model in microsurgery technology training which provides standardize training for surgical residents - Xian-Shun HAN; Qian-Jin ZHENG; Xiang HU; Sheng-Xiang TAO (Yixue xinzhi zazhi)
Objective Aiming at to evaluate the standardized training for surgical resident students, this paper discusses the effect of the team based learning (TBL) teaching model applied to microsurgical technology train-ing.Methods 48 surgical resident trainees undergoing standardized training in Zhong Nan Hospital of Wuhan University from 2018 to 2019 were trained in microsurgery technology using the TBL teaching model. The training content included three parts: small vessel anastomosis training, cadaveric demonstration of tissue flap transplantation and clinical operation teaching. A questionnaire survey was administered before and after the training covering the training of small vessel anastomosis and the demonstration of tissue flap transplantation cadavers which included the understanding of relevant knowledge. The practices of the technical operation of small vessel anastomosis and clinical microsurgical operations performed by the trainees before and after the training were also assessed and scored.Results The number of trainees who fully understood the small vessel anastomosis technology and tissue flap trans-plantation technology increased from 0 before training to 48 after training; the number of trainees who felt it was very difficult and were unable to grasp it decreased from 24 to 3 after training. After training, the average total score of small vessel anastomosis technique operation (11.54±1.88 vs. 7.40 ±1.65, P